2010
DOI: 10.1002/jhet.405
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and heterocyclization of carbohydrazides

Abstract: magnified image The review summarizes recent literatures dealing with the synthesis of carbohydrazide derivatives, chemical reactions and their applications in the synthesis of important heterocyclic as well as fused heterocyclic compounds. J. Heterocyclic Chem., (2010).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…[5]. A typical procedure for the preparation of unsubstituted hydrazides is the treatment of the corresponding carboxylic ester with NH 2 NH 2 ·H 2 O [1] [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5]. A typical procedure for the preparation of unsubstituted hydrazides is the treatment of the corresponding carboxylic ester with NH 2 NH 2 ·H 2 O [1] [5].…”
mentioning
confidence: 99%
“…[5]. A typical procedure for the preparation of unsubstituted hydrazides is the treatment of the corresponding carboxylic ester with NH 2 NH 2 ·H 2 O [1] [5]. In a recent publication we have reported on the application of this method for the preparation of diverse types of unsubstituted hydrazides containing in their structure the imidazole ring [6].…”
mentioning
confidence: 99%
“…In the case of carbohydrazides, only a few reactions with isoselenocyanates have been reported to date [4a][4b] [5]. Whereas, to the best of our knowledge, carbohydrazides derived from heterocyclic carboxylic acids have not yet been used in such reactions [6], reactions of benzohydrazide with aliphatic and aromatic isoselenocyanates are known [4a][4c], and in a recent study, selenosemicarbazides obtained thereby were shown to form 1,3,4-oxadiazole derivatives upon heating in DMF solution to 100° in the presence of air-oxygen [5]. This reaction was accompanied by the formation of elemental Se.…”
Section: Introduction -Isoselenocyanates Are Well Known As Versatilementioning
confidence: 99%
“…In the case of the bis-heterocycle 8, treatment with HCOONH 4 and Pd/C in MeOH gave the debenzylated product 12.…”
mentioning
confidence: 99%
“…On the other hand, carbohydrazides are known as versatile starting materials for the synthesis of five-and six-membered heterocycles containing N, O, and S-atoms [4]. In our recent publications, the preparation and reactivity of 3-oxidoimidazole-4-carbohydrazides 1 as well as prolinehydrazides 2 were described [5][6][7][8].…”
mentioning
confidence: 99%